Comparison of patties produced using meat from various animal species with black-eyed peas as the partial meat substitute - Mohammad Rashedi, Ismail Fitry; Ming, Fu; Basri, Nursyazwina; Ishamri, Ismail (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2024)
Incorporating plant-based ingredients as meat substitutes can be a strategy to reformulate healthier and more environmentally sustainable meat products. However, meat species variations could lead to different physicochemical and sensory characteristics of the final products. This study aimed to evaluate the physicochemical, sensory, and microstructural properties of patties made from different meat species [chicken (CB), beef (BEB), mutton (MB), and buffalo (BFB)] and substituted with 50% black-eyed peas compared to 100% black-eyed peas (BEP) as the control. An array of physicochemical properties was evaluated, encompassing cooking yield, shrinkage, water holding capacity (WHC), pH, proximate composition, texture, gel strength, and colour. Furthermore, scanning electron microscopy and sensory evaluation were employed to elucidate the microstructural modifications and sensory attributes of the samples. The results reveal significant differences in proximate composition, WHC, and textural properties across the meat species. CB exhibited a higher lightness, cooking yield and softer texture than other samples, which displayed better water retention. Whereas BEB and BFP were harder and chewier. The BEB resulted in lower gel strength and less intact structure, as evidenced by microstructure images and texture profile analysis (TPA) results. No significant difference in sensory traits exists between different meat species. Despite the overall acceptability of BEB being the highest, the MB was the lowest. The composition, texture, and sensory features of chicken and beef with the incorporation of BEP make them viable candidates for use in the development of healthy patties.